The Anesthesiologist's Perspective and Experience in Global Congenital Cardiac Surgery: Results of a Survey of the Congenital Cardiac Anesthesia Society Membership. (March 2022) - Hubbard, Richard M.; Buchbinder, Lindsey B.; Tobias, Joseph D.; Zabala, Luis M; Latham, Gregory J.; Gautam, Nischal K.
Anesthesiologists are important components of volunteer teams which perform congenital cardiac surgery in low-resource settings throughout the world, but limited data exist to characterize the nature and breadth of their work. A survey of Congenital Cardiac Anesthesia Society (CCAS) members was conducted with the objective of understanding the type of voluntary care being provided, its geographic reach, the frequency of volunteer activities, and factors which may encourage or limit anesthesiologists' involvement in this work. The survey was completed by 108 participants. Respondents reported a total of 115 volunteer trips during the study period, including work in 41 countries on 5 continents. Frequent motivating factors to begin volunteering included invitations from charitable groups, encouragement from senior colleagues, and direct connections to individual locations. Discouraging factors included familial responsibilities, the need to use vacation time, and a lack of support from home institutions. The year 2020 saw a marked decrease in reported volunteer activity, and respondents reported multiple pandemic-related factors which might discourage future volunteer activities. The results of this study demonstrate the global reach of anesthesiologists in providing care for children having cardiac surgery. It also offers insights into the challenges faced by interested individuals, many of which are related to a lack of institutional support. These challenges have only mounted under the COVID-pandemic, leading to a dramatic downturn in volunteer activities. Finally, the survey reinforces the need for better coordination of volunteer activities to optimize clinical impact.